Band gap manipulation and physical properties of preferred orientation CuO thin films with nano wheatear array. Issue 1 (January 2018) - Chen, Yue; Zhang, Lin; Zhang, Haotian; Zhong, Kehua; Zhao, Guiying; Chen, Guilin; Lin, Yingbin; Chen, Shuiyuan; Huang, Zhigao
Abstract: In this work, CuO ( 1 ¯ 1 1 ) preferred orientation thin films with nano wheatear array have been prepared by using reactive magnetron sputtering. Their structures, physical properties were measured, and the surface energies of CuO films were calculated by first-principle calculations. Especially, single nanowire electronic measuring method based on conductive atomic force microscopy (C-AFM) and Kelvin probe force microscopy (KPFM) were developed. The prepared CuO films with nano wheatear array have good crystallinity. Here, wheatear is an ear of wheat, and the morphology of nanowire is similar to that of the wheatear. It is found that the band gaps of CuO films can be modulated from 1.54 to 1.25 eV by changing length of nano wheatear. Moreover, the measured results by KPFM show the existence of the p -type carrier, the decrease of the band gap with increasing length of nano wheatear. At the same time, the applied electric field ( E) dependence of the current density ( J ) for single nano CuO wheatear was measured by C-AFM. The experimental results in the injection and direct tunnel regimes indicate that, with increasing length of nano CuO wheatear, the work function is enhanced and the band gap is decreased. The measured results on work function and band gap by C-AFM are consistent with those by KPFM. At last, it is suggested that KPFM and C-AFM can provide both effective methods in measuring the band gap of the semiconductor.